Highly efficient removal of trace level dieldrin from water resources utilizing a cerasomal strategy. Issue 26 (16th June 2016) - Feng, Shanshan; Ma, Fang; Liu, Renfa; Li, Shouzhu; Li, Xiaoda; Jin, Yushen; Fu, Guanglei; Yue, Xiuli
Abstract : In this work, a novel cerasomal removal strategy for persistent organic pollutants (POPs) from water resources is proposed for the first time using the synchronous cerasome-forming process of an organic–inorganic composite lipid to capture and remove POPs. Abstract : In this work, a novel cerasomal removal strategy for persistent organic pollutants (POPs) from water resources is proposed for the first time using the synchronous cerasome-forming process of an organic–inorganic composite lipid to capture and remove POPs. It is proposed that hydrophobic POPs could be captured in the hydrophobic bilayer of the synchronously formed cerasomes in aqueous environments with dieldrin as the model POP. The method was found to be highly efficient in the removal of trace level dieldrin in a range of 5 μg L −1 to 60 μg L −1 . Moreover, with the involvement of superparamagnetic Fe3 O4 nanoparticles, a much more simple and efficient magnetic removal of POPs was achieved. In comparison with the non-magnetic cerasomal method, the removal rate of dieldrin of the magnetic cerasomal strategy was elevated by ∼10% at a high dieldrin concentration range of 80 μg L −1 to 160 μg L −1 . The greater removal efficiency of the magnetic cerasomal strategy was assumed to be due to the accumulating effect of the hydrophobic sites on hydrophobic dieldrin due to hydrophobic dieldrin molecules being captured in the hydrophobic domain of the lipid bilayers, based on the principle of "like prefers like". Herein, these results demonstrate the great promise of the cerasomal method, particularly the magnetic cerasomal strategy, as a promising novel cleaning method for POPs from water resources. In addition, all materials involved in non-magnetic cerasomes and magnetic cerasomes are biosafe, thus avoiding the problem of secondary environmental pollution. This paper also paves the way to bring magnetic cerasomes from fundamental research to practical wastewater treatment applications.